REFLECTION ON DANCE TECHNIQUES EDUCATION IN PHYSICAL EDUCATION GRADUATION COURSE AT UFPB (Fiep Bulletin - online, 2014)
In João Pessoa city (PB - Brazil) there is a total lack situation of professionals with an appropriate formation in Dance, due to the lack of technician or superiors courses in the area. The following reflection is regarding the insertion of dance disciplines in the school, issue endorsed for the great article number and papers in this direction, and the performance of the permitted teachers in physical education as one of the appropriate professionals to teach this content in the city reality. Inside of the presented proposal, the school dance education does not have the function to form dancers, but it fulfills a social and transforming function. This reflection regards the education of dance techniques in the Physical Education course at the UFPB (Paraiba Federal University), in disciplines of Dance Teaching Methodology, understanding that the professor will not apply dance techniques in the school, as well as the time of contact (only six months of learning period) with this discipline and other similar ones, will not inform or train he/she in the motor and theoretical aspects to exert this function.
Keywords: dance; physical education; education